2017
DOI: 10.1104/pp.17.01401
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Can Be Reduced in Crop Canopies with Little Penalty to Photosynthesis

Abstract: The hypothesis that reducing chlorophyll content (Chl) can increase canopy photosynthesis in soybeans was tested using an advanced model of canopy photosynthesis. The relationship among leaf Chl, leaf optical properties, and photosynthetic biochemical capacity was measured in 67 soybean (Glycine max) accessions showing large variation in leaf Chl. These relationships were integrated into a biophysical model of canopy-scale photosynthesis to simulate the intercanopy light environment and carbon assimilation cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 74 publications
7
67
0
Order By: Relevance
“…Concerning the nitrogen demands, our results are in line with the simulations of Walker et al () who demonstrated that similar rates of canopy photosynthesis can be maintained with 9% savings in leaf nitrogen resulting from decreased Chl. In our study, higher nitrogen savings were observed, as MinnGold had 24% less N per unit leaf area than Eiko (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning the nitrogen demands, our results are in line with the simulations of Walker et al () who demonstrated that similar rates of canopy photosynthesis can be maintained with 9% savings in leaf nitrogen resulting from decreased Chl. In our study, higher nitrogen savings were observed, as MinnGold had 24% less N per unit leaf area than Eiko (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…The increased photochemical efficiency of individual leaves of the mutant (Figure ) would suggest that for a given amount of APPFD CANOPY , GPP should have been higher in MinnGold than in Eiko. However, this was not the case (Figure ), suggesting that the higher photochemical efficiency was enough to only offset the lower light absorption (Walker et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Decreasing leaf chlorophyll content to allow more radiation into the canopy is a possible route to improving canopy photosynthetic efficiency (Ort et al ., , ). This should result in minor reductions in overall photosynthetic efficiency while significantly saving on nitrogen input (Slattery et al ., ; Walker et al ., ). Therefore, this trait has received considerable attention in GWAS (Dhanapal et al ., ; Hao et al ., ; Lin et al ., ; Wang et al ., ).…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 97%
“…In the past 15 years, attempts to improve plant photosynthetic efficiency have focused on identifying the efficiency bottlenecks in photosynthesis and then bio‐engineering photosynthetic pathways to overcome them (Long et al ., ). This approach has led to suggestions, amongst others, to modify specific subunits of photosystem II (PSII) to optimise light‐harvesting capacity (Long et al ., ; Ort et al ., ; Walker et al ., ), improve the catalytic properties of Rubisco (Carmo‐Silva et al ., ) and transplant the C4 photosynthesis machinery into C3 plants (Crovshoff and Hibberd, ; Schüler et al ., ). Application of this strategy has been successful.…”
Section: Introductionmentioning
confidence: 99%
“…On the flipside, Walker et al (2018) address the longheld hypothesis that photosynthesis can be increased by limiting the chlorophyll content of upper leaves of the canopy, where photosynthetic activity is readily maximized at low levels of solar radiation. Their simulations for soybean (Glycine max) predict that reductions in chlorophyll can provide a savings of nearly 10% of leaf nitrogen without compromising photosynthetic assimilation at the canopy scale.…”
Section: Photosynthesis: Maximizing Flexibility and Outputmentioning
confidence: 99%